Dependent Adult Abuse Trends in Iowa, 1984 to 2023 - Jeanette M. Daly; John W. Ely; Gerald J. Jogerst (SAGE Publishing, 2024)
Introduction: Little is known about trends in the incidence of dependent adult abuse (DAA). Objectives: To determine the annual incidence of DAA in Iowa from 1984 to 2023. Trends in abuse rates were evaluated for their associations with calendar year, number of caseworkers and abuse laws, political party, and unemployment. Methods: Iowa Department of Health and Human Services DAA reports, investigations, and substantiations were analyzed. Report data were available for 10 years. Investigation and substantiation data were available for 40 years. Long-term trends over time were described and associations between abuse rates and number of caseworkers and abuse laws, political party, and unemployment were explored. Results: Both investigations and substantiations increased from 50 to 182 per 100 000 adults and 17 to 38 per 100 000 adults between 1984 and 2023, respectively. Increasing calendar year and Democratic party majority in the Iowa legislature were positively and independently associated with investigated and substantiated abuse rates. An inverse correlation between the proportion of reports that were investigated and the proportion of investigations that were substantiated (Spearman's rho = −.81; P  < .01) was found. Conclusions: During the 40-year study period, investigated and substantiated cases of DAA in Iowa have been steadily increasing.